Supercritical fluids as antisolvents and transport media - O'Neil, S.A. (2003)
This thesis contains details of experiments involving the use of supercritical fluids (SCF) and high pressure liquids acting as antisolvents and transport media. The thesis is divided into six Chapters, each detailing different aspects of SCF technology.